Risk of reoperation in bioprosthetic valve patients with indication for long-term anticoagulation. Results from the observational retrospective multicentre PLECTRUM study. Issue 2 (27th August 2018) - Poli, Daniela; Antonucci, Emilia; Pengo, Vittorio; Grifoni, Elisa; Maggini, Niccolò; Testa, Sophie; Lodigiani, Corrado; Insana, Antonio; Marongiu, Francesco; Barcellona, Doris; Paparo, Carmelo; Bucherini, Eugenio; et al.
Abstract : Objective: Several factors should be considered when a prosthetic heart valve, bioprosthetic valve (BV) or mechanical valve is to be implanted: thrombogenicity, life expectancy and the risk of reoperation. Methods: We conducted an observational retrospective multicentre study among Italian Thrombosis Centers on patients with BV on long-term vitamin K antagonist (VKA) treatment to evaluate the risk of reoperation and the rate of bleeding and thrombotic events. Results: We analysed 612 patients (median age 71.8 years) with BV on long-term VKA treatment for the presence of atrial fibrillation (AF) (78.4%) or other indications (21.6%). Thirty-four major bleeding events (rate 1.1×100 patient-years) and 29 thromboembolic events (rate 0.9×100 patient-years) were recorded, and 46 patients (rate 1.5×100 patient-years) underwent reoperation. The rate of reoperation was higher among younger patients: 32.9% in patients <60 years and 3.9% in patients ≥60 years (relative risk (RR) 3.8, 95% CI 2.1 to 7.2; p=0.0001). When patients were analysed according to age <65 or ≥65 years and <75 or ≥70 years, younger patients still were at higher risk for reoperation (RR 3.1, 95% CI 1.7 to 6.0 and 3.7, 95% CI 1.7 to 8.6, respectively). Conclusions: Our findings suggest that the threshold of 65 years for implanting a BV should be carefully evaluated, considering the high risk for reoperation and the high risk of AF occurrence with persisting need for long-term anticoagulation. The high risk for reoperation of young patients implanted with BV and the availability of a safer and easier way to conduct VKA treatment, such as the use of point-of-care devices, should be considered when the type of valve must be chosen.